Do tradeoffs among dimensions of women’s empowerment and nutrition outcomes exist? Evidence from six countries in Africa and Asia - Quisumbing, Agnes R.; Sproule, Kathryn; Martinez, Elena M.; Malapit, Hazel J. (Elsevier, 2021)
Although women’s empowerment and gender equality are often linked with better maternal and child nutrition outcomes, recent systematic reviews find inconclusive evidence. This paper applies a comparable methodology to data on the Women’s Empowerment in Agriculture Index (WEAI), an internationally-validated measure based on interviews of women and men within the same household, from six countries in Africa and Asia to identify which dimensions of women’s empowerment are related to household-, woman-, and child-level dietary and nutrition outcomes. We examine relationships between women’s empowerment and household-level dietary diversity; women’s dietary diversity and BMI; and child-related outcomes, controlling for woman, child, and household characteristics. We also test for differential associations of women’s empowerment with nutrition outcomes for boys and girls. We find few significant associations between the aggregate empowerment scores and nutritional outcomes. The women’s empowerment score is positively associated only with child HAZ, while lower intrahousehold inequality is associated with a higher likelihood of exclusive breastfeeding and higher HAZ but with lower BMI. However, analysis of the subdomain indicators finds more significant associations, suggesting that tradeoffs exist among different dimensions of empowerment. Women’s empowerment accounts for a small share of the variance in nutritional outcomes, with household wealth and country-level factors accounting for the largest share of the variation in household and women’s dietary diversity. In contrast, most of the variation in child outcomes comes from child age. Improving nutritional outcomes requires addressing the underlying determinants of poor nutrition in addition to empowering women and improving gender equality.